2019–2020 Florida Citrus Production Guide: Asian Citrus Psyllid - Lauren Marie Diepenbrock; Jawwad Qureshi; Lukasz Stelinski; Philip A. Stansly (EDIS)
The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama, was first detected in Florida in 1998 and has since become the key pest of citrus due to its role as vector of the pathogen that causes citrus greening disease, also known as huanglongbing (HLB). The HLB pathogen, Candidatus liberibacter asiaticus (Clas), is transmitted and spread by adult ACP but acquired primarily by nymphs. This 7-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Lauren Marie Diepenbrock, Jawwad Qureshi, Lukasz Stelinski, and Philip A. Stansly, and publsihed by the Entomology and Nematology Department, March 2019.